2016
DOI: 10.1080/21565503.2016.1148058
|View full text |Cite
|
Sign up to set email alerts
|

Civic engagement and political participation among American Indians and Alaska natives in the US

Abstract: Within the growing literature seeking to understand civic and political engagement among racial and ethnic minorities, our understanding of political behavior among American Indian and Alaska Native’s (AI/AN) remains limited. We use the Current Population Survey Civic Engagement and Voting and Registration supplements (2006-2012) to compare AI/AN voter registration, voting, and overall civic engagement to other racial and ethnic groups and to assess whether factors that predict higher levels of civic engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Tribes differ as to how they view participation in U.S. politics; some see it as “virtual acts of treason” and others as a significant way to protect tribal interests (Wilkins and Stark, :170). Several scholars have also noted that unlike other minorities in the United States, the goals of American Indians are often less about being incorporated into mainstream political and economic society, and more about the maintenance of their tribal sovereignty (Wilkins and Stark, ; Huyser, Sanchez, and Vargas, ; Kahn, ), and many tribal leaders do not trust state governments or feel their vote will make a difference (Wang, :8). In addition, the development of a group consciousness may have been negatively affected by the U.S. policy of assimilation, which resulted in many American Indians losing much of their tribal culture.…”
Section: Group Consciousnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Tribes differ as to how they view participation in U.S. politics; some see it as “virtual acts of treason” and others as a significant way to protect tribal interests (Wilkins and Stark, :170). Several scholars have also noted that unlike other minorities in the United States, the goals of American Indians are often less about being incorporated into mainstream political and economic society, and more about the maintenance of their tribal sovereignty (Wilkins and Stark, ; Huyser, Sanchez, and Vargas, ; Kahn, ), and many tribal leaders do not trust state governments or feel their vote will make a difference (Wang, :8). In addition, the development of a group consciousness may have been negatively affected by the U.S. policy of assimilation, which resulted in many American Indians losing much of their tribal culture.…”
Section: Group Consciousnessmentioning
confidence: 99%
“…The little bit of research that has examined American Indians’ voting suggests they vote at low levels (Peterson, ; McCool, ; Ritt, ; Peterson, ; Kunitz and Levy, ; Wang, , but see Huyser, Sanchez, and Vargas, ) and it is unclear what role SES plays in their voting levels. While Peterson () found that the voting gap did not disappear when individuals’ sex, education, income, and age were taken into account, more recently Huyser, Sanchez, and Vargas () found American Indians voted at similar levels as whites, once SES was considered. Research on their party attachment, which examines voting behavior as well as party identification, generally finds that American Indians are likely to be Democrats (Min and Savage, , ; McClain and Stewart, :100; Herrick and Mendez, ; Ritt, ; but see McCool, ; Kunitz and Levy, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past couple decades, there has been a dramatic increase in the quality and quantity of academic research on political participation among racial and ethnic minorities in the United States, but only recently have scholars begun to consider unique factors that impact Native American political engagement. Research (Huyser, Sanchez, and Vargas, 2017;Peterson, 1997) shows that Native Americans' registration and voting rates are lower than other populations, but the turnout gap appears to be declining (Skopek and Garner, 2014). Also, the electoral context matters, with turnout higher in elections that have greater local impact (Huyser, Sanchez, and Vargas, 2017;Native American Voting Rights Coalition, 2018).…”
mentioning
confidence: 99%
“…Research (Huyser, Sanchez, and Vargas, 2017;Peterson, 1997) shows that Native Americans' registration and voting rates are lower than other populations, but the turnout gap appears to be declining (Skopek and Garner, 2014). Also, the electoral context matters, with turnout higher in elections that have greater local impact (Huyser, Sanchez, and Vargas, 2017;Native American Voting Rights Coalition, 2018). Finally, Wilkins and Stark (2011) forcefully argue that participation among American Indian/Alaska Native populations is affected by their unique civic status as members of indigenous nations as opposed to being racial minorities.…”
mentioning
confidence: 99%